2019
DOI: 10.1101/712554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diurnal variation in xylem water isotopic signature biases depth of root-water uptake estimates

Abstract: Total word count (ex. summary, references and legends): 6 932 words 25 of which: Summary (198 words); Introduction (698 words); Material and Methods (2 922 words); Results (1 138 words); Discussion (1 556 words) Conclusion (222 words); Acknowledgement (128 words) Number of color figures: 7 figures 30 Number of Tables: 2 tables Supplementary information: 7 (color Fig S1-S5 + Table S1-S2) 2 Summary  Stable water isotopes are a powerful and widely used tool to derive the depth of root water uptake (RWU) in ligni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…First, we assumed that extracted stem water was representative of mobile tree‐stored water in order to maintain a simplistic approach to the numerical representation of tree‐stored water. As demonstrated by Zhao et al () and De Deurwaerder et al (), there exists the possibility of isotopic variations within stems. Low variation in observed δ XYLEM of both hemlock and beech at each location (Figures and ) suggested that this simplification was reasonable.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…First, we assumed that extracted stem water was representative of mobile tree‐stored water in order to maintain a simplistic approach to the numerical representation of tree‐stored water. As demonstrated by Zhao et al () and De Deurwaerder et al (), there exists the possibility of isotopic variations within stems. Low variation in observed δ XYLEM of both hemlock and beech at each location (Figures and ) suggested that this simplification was reasonable.…”
Section: Discussionmentioning
confidence: 91%
“…Rothfuss and Javaux (), Barbeta, Ogée, and Peñuelas (), Penna et al (), De Deurwaerder et al (), and Wang et al () highlighted conceptual limitations of the EMMA approach in that we must assume that measured soil water isotopic compositions are representative of available water sources at the time of RWU. Goldsmith et al () demonstrated that spatial and temporal variability in soil water can influence RWU depth estimates.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adding this to SF measurements gauging different roots (Lott et al, 1996) and analyses of stable isotope concentration in the xylem water (Rothfuss and Javaux, 2017) could avoid overly simplistic assumptions about soil water availability and mixing. Analyses with higher temporal resolution could also elucidate further details about diurnal variations in xylem water isotopic signatures (De Deurwaerder et al, 2019). Moreover, higher spatial coverage and resolution using hydrogeophysical, quantitative measurements like time-lapse ground penetrating radar (Allroggen et al, 2017;Jackisch et al, 2017) would enable further analyses of the active rhizosphere and its geometry.…”
Section: Discussionmentioning
confidence: 99%